Comparison of Urban Forest Inventory & Management Software Systems - Michael G. Andreu; Erin M. Brown; Melissa H. Friedman; Robert J. Northrop; Mary E. Thornhill (EDIS)
FOR-226, a 13-page illustrated fact sheet by Michael G. Andreu, Erin M. Brown, Melissa H. Friedman, Robert J. Northrop, and Mary E. Thornhill, examines many of the tree inventory software systems available as of 2009. It provides up-to-date information about previously existing tree inventory software systems as well as those recently launched. Includes references. Published by the UF School of Forest Resources and Conservation, August 2009.